COMPARISON OF THE PROBLEM BASED LEARNING (PBL) MODEL WITH THE DISCOVERY-INQUIRY FOR THE STUDENT MATHEMATICS LEARNING MODEL AT SMPN 3 SINJAI - Latri Aras; Ramlan Mahmud; Nurlaela Latif (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2022)
This research is to find out the comparism of the Problem Based Learning (PBL) model with the Discovery-Inquiry model on the 7th grade students of SMP Negeri 3 Sinjai year 2020/2021. This research used two classes chosen by Purposive Sampling technique. Both classes were given different treatments with the same material, that was One Variable Linear Equations. To obtain the data, the researcher used a test which had been tested through validity test and reliability test. After that, the data were analyzed with normality test, homogeneity test, and hypothesis test (Independent Sample T-Test). The result of this research indicated that there are some differences in the learning result using the Problem Based Learning (PBL) model and the Discovery-Inquiry model on the 7th grade students of SMP Negeri 3 Sinjai year 2020/2021The average grades of the class using the Problem Based Learning model was higher than the Discovery-Inquiry model. This result indicates that the Problem Based Learning model is better than the Discovery-Inquiry model.